Tuberculosis Screening and Active Tuberculosis among HIV-Infected Persons in a Canadian Tertiary Care Centre - Paul Brassard; Travis Salway Hottes; Richard G Lalonde; Marina B Klein (Canadian Journal of Infectious Diseases and Medical Microbiology)
RATIONALE: HIV infection increases the risk of reactivation of latent tuberculosis (TB). The present study evaluates how latent TB is detected and treated to determine the effectiveness of screening in HIV-infected patients with diverse risk profiles.